(untitled) (Research, Society and Development, 2022)
ThermoPlastic Vulcanized (TPV) is a class of polymeric materials capable of combining the high elasticity of elastomers with the recycling of thermoplastics. The production of TPV with recycled material contributes to the reduction of polymeric waste on the planet, reducing its environmental impact. In this study, recycled TPV samples were produced by combining recycled polyethylene and waste tire powder. The TPV samples were obtained in an internal mixer, changing the processing conditions, during the vulcanization and stabilization stages of the final torque. The results showed that by reducing the processing speed from 60 to 40 rpm, TPV samples were obtained with higher tensile strength and low swelling in oil. ANOVA statistical analysis confirmed that significant changes occurred due to processing speed variations. The DUNCAN mean parity statistical model was used for comparisons between pairs of TPV samples. Frequency sweeping rheological analysis confirmed the effect of adding tire powder on the samples’ elastic modulus. There were no changes in the viscous and elastic modules of the samples. The absence of significant changes in the final morphology of the TPV samples was attributed to the tire powder size. The increased properties of TPV samples are attributed to new crosslinking of the elastomeric phase during dynamic vulcanization.